Interaksi Sosial Islam dan Konghucu - Hamzah Khaeriyah (TASAMUH: Jurnal Studi Islam, 2017)
Social interaction is very useful in studying various problems in society. In Indonesia forms of social interaction takes place between the various tribes, nations, between the educated classes with denominations. The social interaction is the key to all social life. Because without interaction, there can be no life together. The meeting of individuals in the flesh will not produce social life within a social group. The social interaction plays between members and groups in society based on the values, norms believed by the public. One of the values or norms that are believed by the public is derived from the teachings of their religion. Religion here can be seen as the values that are believed by the public and can be seen as a factor that encourages social interaction among religious followers. Because religion, seen as a social phenomenon is reflected by the social interaction that is carried by its adherents, then religion has a variety of functions: the function of social solidarity, the function of giving meaning to life, social control function, the function of social changes and psychological support functions. Religion provides the inspiration and paves the way to social change. Religion provides the inspiration and paves the way to social change. Religious values provide moral standardization of how a number of existing community settings should be measured and how it should be